2022
DOI: 10.1021/acs.biomac.2c01157
|View full text |Cite
|
Sign up to set email alerts
|

Silk Fibroin-Based Tough Hydrogels with Strong Underwater Adhesion for Fast Hemostasis and Wound Sealing

Abstract: Rapid and strong adhesion of hydrogel adhesives is required for instant wound closure and hemostasis. However, in situ hydrogel formation and sufficient adhesion at target tissue sites in biological environments are severely compromised by the presence of blood and body fluids. In this work, an underwater adhesive hydrogel (named SHCa) is fabricated with rapid in situ gelation, enhanced mechanical toughness, and robust underwater adhesion. The SHCa can undergo rapid UV irradiation-induced gelation under water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…The studies confirmed that the SF-based hydrogel had been found to be biocompatible in biomedical applications without causing any long-term inflammatory reactions . Additionally, the research done previously indicates that SF offers hemostasis, which is very beneficial to wound healing progress. , In addition, it promotes the recruitment of various types of cells, such as neutrophils, macrophages, endothelial cells, fibroblasts, and keratinocytes, and facilitates the proliferation of skin fibroblasts …”
Section: Applications Explored To Datesupporting
confidence: 58%
See 3 more Smart Citations
“…The studies confirmed that the SF-based hydrogel had been found to be biocompatible in biomedical applications without causing any long-term inflammatory reactions . Additionally, the research done previously indicates that SF offers hemostasis, which is very beneficial to wound healing progress. , In addition, it promotes the recruitment of various types of cells, such as neutrophils, macrophages, endothelial cells, fibroblasts, and keratinocytes, and facilitates the proliferation of skin fibroblasts …”
Section: Applications Explored To Datesupporting
confidence: 58%
“…In the long term, SFMA increased the number of vascular structures and collagenous tissue while decreasing the number of infiltrating macrophages, reflecting its biocompatibility. Based on the in vivo , SFMA has proven to be effective at providing secure and long-lasting sealing due to its excellent adhesive properties, hemostatic properties, and wound healing properties. , The SFMA also demonstrated good biocompatibility and long-term degradation, so it was not necessary to retreat or remove it from the injury site …”
Section: Applications Explored To Datementioning
confidence: 99%
See 2 more Smart Citations
“…The intrinsic hemostasis is primarily efficient in stopping bleeding for minor injuries but is inadequate for conditions involving massive hemorrhage, which typically requires external hemostatic agents. Several well-established hemostatic agents, including injectable hydrogels, microporous sponges, instant swelling superabsorbents, and self-propelling Janus particles have resulted in effective hemostasis. Particularly, functional hydrogels are promising as hemostatic materials in effectively promoting both blood clotting and wound healing. Moreover, these hydrogel fabrication technologies have enabled the engineering of bioadhesives with the ability to seal wounds on-demand. However, the hydrophilic nature and swelling behavior of hydrogel bioadhesives result in poor performance in wet and dynamic environments. Therefore, water-insoluble complex based on liquid–liquid phase separations could be alternatives for wound sealing in wet conditions. The innovative technique of coacervate engineering, utilizing liquid–liquid phase separations, has proven to be highly effective in facilitating efficient compartmentalization of polymers. , Developments based on coacervation including foams-stabilized coacervation, multicomponent complex coacervation, and responsive complex coacervation strategies could enhance the wound-sealing activity under wet environments. Importantly, the hemostatic powder derived from coacervates can rapidly absorb the interfacial water from wet environments .…”
Section: Introductionmentioning
confidence: 99%